Kerjasama Resorts World Berhad dengan Kementerian Kebudayaan, Kesenian dan Warisan (KeKKWa) dalam mengembangkan persembahan kaum cina. Kajian kes :pertandingan tarian singa antarabangsa ke-7 - Chan, Mee Chin (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The 7th Genting World Lion Dance Championship is a Chinese dance performance of the Kuala Lumpur Festival 2006. The purpose of the research is to study the effectiveness of the first joint effort by Resorts World Berhad and the Ministry of Culture , Arts and Heritage Malaysia in presenting the 7th World Lion Dance Championship and promote the Chinese performing arts.